Predictive value of cord blood bilirubin in development of neonatal hyperbilirubinemia - Choubey, Bharati P; Kakodia, Aditi; Pal, Pankaj; Agrawal, Amit (Indian Journal of Child Health, 2018)
Introduction: The early detection of neonatal hyperbilirubinemia (NNH) can be done by various methods; however, the most reliable is cord blood bilirubin (CBB). Objective: The objective of this study is to evaluate the predictive value of the CBB levels for the subsequent hyperbilirubinemia in healthy term newborns and its association with various maternal and neonatal factors. Materials and Methods: Two hundred healthy term-neonates between 37 and 42 weeks of gestation were included in the study. A thorough antenatal, perinatal, and natal history was obtained. Cord blood was collected from all newborns, and the samples were sent for the estimation of serum bilirubin, blood grouping, and Rh typing. Results: Various risk factors such as gender difference (p